Morality and money: a look at how the respectable community battled the sporting community over prostitution in Kansas cowtowns, 1867-1885 - Smith, Jessica K. (Kansas State University, 2013)
In 1867, Abilene became the first of Kansas’ cattle towns. For the next two decades, Kansas would be the transfer point in bringing Texas cattle herds to market in northern cities, all facilitated by the expansion of railroad lines in the state. For town boosters, the cattle trade was a lucrative source of economic development. But as Abilene was soon to discover, the cattle trade also brought with it, literally, the “evils of the trade,” a whole sub-community of brothels, saloons, and dance halls. The arrival of that vice fostered immediate and often outraged citizen protests. Much of the history of cattle towns in Kansas is therefore the story of “respectable” citizens fighting the vice in their midst. This thesis examines Abilene, Kansas, in particular, and especially focuses upon one peculiar circumstance: Abilene was the only cowtown that ridded itself of vice by deliberately asking the cattle trade to leave. Abilene’s experience also reveals the mobility of the sporting community; prostitutes notorious in Abilene turned up in many other Kansas cattle town. This thesis therefore continues by examining this mobile sub-culture of prostitutes including their living conditions, their confrontations with municipal government, and the outrage they inspired wherever they went.
Keywords: Prostitution; Kansas; Cowtowns; Abilene; History; American History (0337)